Pengaruh Pemberian Timbal (Pb) Dengan Konsentrasi Berbeda Terhadap Klorofil, Kandungan Timbal Pada Akar Dan Daun, Serta Struktur Histologi Jaringan Akar Anakan Mangrove Rhizophora mucronata - Siahaan, Michael Teguh Adiputra; Ambariyanto, Ambariyanto; Yulianto, Bambang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
condition of mangroves have decreased over the years. Beside it has been used for human activities, mangrove habitat is also influenced by heavy metal pollution, and one of them is lead (Pb). Among all major mangroves, Rhizophora mucronata is one of the important spesies which also widely distributed. This research aimed to investigate the effect of lead treatment in different concentration to chlorophyll, content of the lead in leaves, root, and root histological structure of R. mucronata seedling. Treatments were done in 30 days, and the concentrations of Pb were 0,1; 1; 10; and 100 ppm. Mangrove seedlings were planted in bucket pot with 50 cm in diameter and 30 cm height, putted in greenhouse that has size 5,5 x 2 x 1,5 m. The result show that Pb treatment until 100 ppm has significant effect on chlorophyll content. Whereas the content of Pb in leaves and root, as well as root histology did not show signficant effect.